Beloved land the world of Emily Carr - Carr, Emily 1871-1945 (Douglas & McIntyre [u.a.], 1996)
Beloved Land: The World of Emily Carr celebrates the art and writing of a great artist who dedicated her life to portraying the powerful majesty of the coastal landscape, the lush rain forest and the monumental totem poles created by the native people of British Columbia. The 40 full-colour paintings chosen for this book from the collection of the Vancouver Art Gallery are among Emily Carr's most popular, and they are accompanied by short quotations from her writing. The introduction by Robin Laurence presents revealing insights into the life of this unconventional and gifted woman.